(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Umbilical Granuloma is a benign abnormality of the umbilicus and can be defined as a moist, fleshy, and pink granulation tissue at the center of the umbili cus. Considering the safe and effective treatment of umbilical granuloma more re cently common salt or NaCl tablets are gaining popularity over conventional meth ods of chemical cauterization with copper sulphate. Therefore, this study aimed to determine the outcome of NaCl tablets in managingUG. Materials and methods: This was a retrospective study and was conducted in the Department of Pediatric Surgery, Bangladesh Shishu Hospital and Institute and other two Private Clinics in Dhaka, Bangladesh during the period from July 2020 to June 2022. In our study, we included 80 patients with clinically evident umbilical granuloma who sought treatment from the investigators and NaCl tablet powder was applied tropically for the treatment. Results: The mean age was 9.88±9.7 weeks. Most (58%) of our patients were male. At the end of the 3rd day, 7th and 28th day, complete regression was found in 76.67%, 81.67%, and 91.67% of cases respectively. The common side effects were local irritation (3.33%) and wound infection (0.83%). At the last follow-up, no recurrence was found in our study patients. The majority (96.67%) of patients showed excellent response to the treatment. Conclusion: In our study, we showed that topical application of NaCl tablet powder could be a good alternative for treating neonatal umbilical granuloma due to its simplicity, safety, and effectiveness. Applying common salt is an easy, and reasonably priced therapy option that doesn’t include synthetic drug use or surgical side effects Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 76-80